Enhancing erythritol production from crude glycerol in a wild-type Yarrowia lipolytica by metabolic engineering - Yang, Shuling; Pan, Xuewei; Wang, Qiang; Lv, Qinglan; Zhang, Xian; Zhang, Rongzhen; Rao, Zhiming (Frontiers in Microbiology, 2022)
Erythritol is a zero-calorie sweetener widely used in the food, pharmaceutical, and medical industries. The availability of expensive raw materials limits the broad-spectrum applications of erythritol. Crude glycerol is the main by-product of biodiesel, and the effective utilization of crude glycerol will help to improve biodiesel viability. The oleaginous yeast Yarrowia lipolytica has been shown to synthesize erythritol from crude glycerol. Previous studies on erythritol production using crude glycerol as a carbon source by Y. lipolytica have mainly focused on optimizing the fermentation process of the mutant Y. lipolytica Wratislavia K1, while metabolic engineering has not been successfully applied. To this end, we engineered the yeast Y. lipolytica to increase the productivity of this strain. Wild strains tolerant to high concentrations of crude glycerol were screened and identified. A series of rational metabolic approaches were employed to improve erythritol production. Among them, the engineered strain Y-04 obtained by tandem overexpression of GUT1 and GUT2 significantly increased glycerol assimilation by 33.3%, which was consistent with the results of RT-qPCR analysis. The effects of GUT1, GUT2, TKL1, and TAL1 overexpression in tandem on erythritol synthesis were also evaluated. The best results were obtained using a mutant that overexpressed GUT1, GUT2, and TKL1 and knocked out EYD1. The final Y-11 strain in a 5-L bioreactor produced 150 g/L erythritol with a yield and productivity of 0.62 g/g and 1.25 g/L/h, respectively. To the best of our knowledge, this is the highest erythritol yield and productivity from crude glycerol ever reported in Y. lipolytica. This work demonstrated that overexpression of GUT1, GUT2, and TKL1 genes and knockdown of EYD1 could be used to improve crude glycerol utilization and erythritol synthesis in Y. lipolytica. The process parameters such as erythritol yield and productivity were significantly elevated, which is valuable for industrial applications. Crude glycerol as a carbon source can enhance erythritol production and effectively inhibit the synthesis of by-products compared to glucose. This indicates a great potential for synthesizing value-added products from crude glycerol by Y. lipolytica.